EVALUATION OF THE MICROTEACHING COURSE PROGRAM USING THE CIPP MODEL: OPTIMIZING DIGITAL TECHNOLOGY TO ENHANCE PROSPECTIVE PHYSICS TEACHERS’ TEACHING READINESS - Warliani, Resti; Sriyati, Siti; Nahadi; Liliawati, Winny; Hamidah, Ida (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2025)
This study aims to evaluate the Microteaching course program in the Physics Education Study Program using the CIPP (Context, Input, Process, Product) evaluation model and to analyze the role of digital technology in enhancing prospective teachers’ teaching readiness. Data were collected through questionnaires, interviews, analysis of the course syllabus (RPS), and video documentation of Microteaching practices. Participants consisted of 19 seventh-semester students, one course instructor, and the Head of the Study Program. The Context evaluation showed that all components of the course syllabus were available and that there was a 100% alignment among Program Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and course content. Regarding Input, students demonstrated good academic prerequisites, as indicated by 90% of them obtaining an A in the Physics Lesson Planning course; however, only 21.1% owned relevant textbooks, and facilities such as a dedicated Microteaching room and documentation equipment still require improvement. The Process evaluation revealed that 100% of students used technology in their Microteaching practices, particularly through presentation media, virtual simulations, and instructional videos, and some of them utilized artificial intelligence (AI) tools to support lesson planning. The Product evaluation indicated that most students achieved high final grades in the Microteaching course and reported positive perceptions of its contribution to their teaching readiness. These findings highlight the importance of strengthening students’ digital literacy, providing adequate facilities specifically designed for Microteaching, and systematically training teaching skills that integrate digital technology in order to further optimize the quality of the Microteaching course.